ASR, Volume 19, n°2, 2015 - Full Issue - journal system (African Sociological Review, 2015)
Contents Editorial .............................................1 General Issue Capital Accumulation, Social Reproduction and Struggle: Rethinking the function of Spatial Planning and Land Use Paul Heller ..................................................2 Research Papers Between the Clinic and the Community: Temporality and Patterns of ART Adherence in the Western Cape Province, South Africa Larkin F., van Wyk B., Stevens P. and Saris A. J. .................................26 Holistic Development: Women’s Civil Society Groups in Nigeria, Ghana and Tanzania Adryan Wallace .......................................................53 La Contribution des jeunes à l’alternance Politique au Sénégal : Le rôle de Bul faale et de Y’en a marre Moda Dieng ......................................................76 Health Inequality in South Africa: A Systematic Review Chinwe C. Obuaku-Igwe ...........................................97 The Socio-economic well-being of Internal Migrants in Agbogbloshie, Ghana Ronald Adamtey, John Ebotui Yajalin and Charles Yaw ..................................133 Successful Ageing Among Elderly Women Living Independently in Central Areas of Pretoria, South Africa Marlize Rabe ............................................................150